Anxiolytic-like actions of buspirone in a runway model of intravenous cocaine self-administration - Ettenberg, Aaron (2006)
In previous work from our laboratory, rats traversing a straight alley for a reward of IV cocaine have been observed to develop ambivalence about entering the goal box. Over trials, animals repeatedly run toward the goal box, stop at the entry point, and then retreat back toward the start box. This unique pattern of retreat behavior has been shown to reflect a form of “approach-avoidance conflict” that stems from the subjects' concurrent positive (cocaine reward) and negative (cocaine-induced anxiety) associations with the goal box. Buspirone, a partial 5-HT(1A) agonist, has been reported to produce anxiolytic-like actions in the clinic, but has had mixed results in experimental tests of anxiety using animal subjects. Since most animal tests of conflict/anxiety employ the administration of foot-shock – a relatively strong aversive stimulus – it was of interest to determine whether buspirone would alter the more subtle approach-avoidance conflict observed in well-trained animals running a straight alley for single daily injections of 1.0 mg/kg IV cocaine. Runway testing consisted of single daily trials that continued until consistent approach-avoidance retreats were exhibited. Each animal was then pretreated 30 min prior to runway testing with vehicle and one of three doses of buspirone (0.0, 1.0, 2.5 or 5.0 mg/kg IP). Testing continued in a counterbalanced manner until all rats had experienced each dose of buspirone with 3 days of cocaine-only trials between each test day. The number of retreats exhibited on each trial served as an index of the approach-avoidance conflict present on that trial. Results clearly demonstrated that buspirone (at the two higher doses) attenuated the retreat behavior of animals approaching a goal-box for IV cocaine – an action consistent with its anxiolytic-like actions in the clinic.